Current sensing probe for condition monitoring Purpose - Ng, Wei Lun (2018)
The high frequency current probe is one of the most valuable and commonly used tools by engineers for measuring and monitoring common and differential mode currents. However, commercially available probes are bulky and expensive. Therefore, this project investigates the possibility of significantly reduce cost and size of current probes by experimenting with toroid ferrite cores available off the shelves. A current probe of lower cost and size with similar performance as commercially available product was built.